Iran in motion : mobility, space, and the Trans-Iranian Railway - Koyagi, Mikiya (Stanford scholarship online., 2021)
"In 1938, the Trans-Iranian Railway was completed by the Pahlavi state of Iran as the country's first national railway. As a "belated" railway project of the interwar period, the Trans-Iranian Railway is often understood in the context of modernization and centralization undertaken by an authoritarian state of Reza Shah Pahlavi. Instead of retelling the story of Reza Shah, this book tells hitherto unexplored stories of mobile individuals, including European imperial officials, Qajar-era diplomats, tribesmen, migrant laborers, technocrats, railway workers, and diverse groups of travelers. Drawing on newspapers, industry publications, travelogues, memoirs, as well as American, British, Danish, and Iranian archival materials, "Iran in Motion" traces divergent imaginations and practices of mobility from the conception of a Trans-Iranian Railway project during the nineteenth-century global transport revolution to its early years of operation on the eve of Iran's oil nationalization movement in the 1950s. By weaving together various individual experiences, this book considers how the infrastructural megaproject reoriented the flows of people, goods and constantly reshaped local, national, and transnational imaginations of space among mobile individuals"--